A novel species of Loculosulcatispora (Sulcatisporaceae, Pleosporales) on Juglans regia from Sichuan, China - Wang, Fei-Hu; Wang, Yan-Lin; Zeng, Qian; Xu, Xiu-Lan; Liu, Yinggao; Yang, Chun-Lin (Phytotaxa, 2023)
A novel species, Loculosulcatispora juglans, dwelling on twigs of the English walnut (Juglans regia), is introduced through a combination of phylogenetic analysis utilizing LSU, SSU, ITS, rpb2, and tef1-α sequence data, as well as morphological characteristics. Multi-locus phylogenetic analysis revealed that L. juglans forms a clade (MLBP/BYPP, 98%/0.95) together with L. hongheensis, L. thailandica, and Parasulcatispora clematidis. L. juglans distinguishes itself from phylogenetically similar species due to its unique characteristics, including exclusively 4-spored asci and larger ascospores encased in a thinner mucilaginous sheath.